What customers expect and perceive from a university services? - Mohd Ali, Hairuddin; Salleh, Mohamad Johdi; Othman, Azam (IIUM Press, 2011)
A case study on a service quality of a faculty in one of the local universities. The study was based on Parasuraman's framework. The most important finding were the weaknesses or short of services quality came from the factor of human interactions.